2021
DOI: 10.1039/d0ra08189b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of some novel 1,2-dihydro-[1,2,4]triazolo[1,5-a]pyrimidines bearing amino acid moiety

Abstract: A new series of [1,2,4]-triazole bearing amino acid derivatives were synthesized under green chemistry conditions and evaluated for their antimicrobial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Thus, the existence of these functional groups leads to lipophilic groups in diverse places on the triazepine, pyrimidine, quinoline, triazole, pyran, and phenyl rings, and hydrophobic reactions of the triazolopyrimidine, furochromenotriazepine, and furochromenoquinoline moieties at the more active site. In current work and previous studies, most types of bacteria and fungi are affected by this class of heterocyclic compounds [ 9 , 10 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Thus, the existence of these functional groups leads to lipophilic groups in diverse places on the triazepine, pyrimidine, quinoline, triazole, pyran, and phenyl rings, and hydrophobic reactions of the triazolopyrimidine, furochromenotriazepine, and furochromenoquinoline moieties at the more active site. In current work and previous studies, most types of bacteria and fungi are affected by this class of heterocyclic compounds [ 9 , 10 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 57%
“…All the newly synthesized compounds of the furochromone derivatives were tested in vitro for their antimicrobial activities at a minimum inhibitory concentration [ 9 , 10 , 33 , 34 , 35 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] versus various bacteria and fungi; the results are shown in Table 1 and Table 2 . Some of these compounds showed high antimicrobial activity, comparable to that of cefotaxime sodium (MIC = 1–4 μmol mL −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that natural products have unique biological functional diversity and chemical diversity, which give them unique advantages in drug molecular design [6–8] . In recent years, the derivation of molecular structures from natural products has been one of the most effective methods to develop and design drugs with unique mechanisms of action [9,10] .…”
Section: Introductionmentioning
confidence: 99%